Informality currencies: a tale of Misha, his brigada and informal practices among Uzbek labour migrants in Russia. (1st September 2016) - Urinboyev, Rustamjon; Polese, Abel
Abstract: This article explores the role of informality among Uzbek construction workers in Russia. We start from a relationship that is based on economic reward and common interests and go on to explore the non-economic components of this relationship. Economically, the workers entrust their supervisor and agree to work for him for a given amount of money. However, this decision is also embedded in a non-economic dimension. All workers, and their master, come from the same village so that an additional layer of social obligations are involved. First, workers are able to receive a treatment that goes beyond economic relations, with favours or more mild attitudes when needed. Second, they are also able to put pressure on the line manager through their families in case things do not work out the way they expected. We use the case study to propose the existence of a non-monetary currency (or even currencies) that complement formal currencies. Money, its symbolism and the power attached to it still play a major role in the relationships and dependencies analyzed here. These points help us in suggesting that relations encompass a wide range of transactions and rituals that go beyond mere economic interest and that cannot be neglected when understanding informality.